2017
DOI: 10.1021/acs.jafc.7b01176
|View full text |Cite
|
Sign up to set email alerts
|

Biofortification with Iron and Zinc Improves Nutritional and Nutraceutical Properties of Common Wheat Flour and Bread

Abstract: The effect of field foliar Fe and Zn biofortification on concentration and potential bioavailability of Fe and Zn and health-promoting compounds was studied in wholemeal flour of two common wheat varieties (old vs modern). Moreover, the effect of milling and bread making was studied. Biofortification increased the concentration of Zn (+78%) and its bioavailability (+48%) in the flour of the old variety, whereas it was ineffective in increasing Fe concentration in both varieties. However, the old variety showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 61 publications
1
22
1
Order By: Relevance
“…In recent years, numerous studies have focused on the qualitative aspects of wheat production to face the widespread malnutrition due to the lack of nutrients in the diet, which leads to the development of pathologies [13][14][15]. There are several biofortification strategies for increasing the concentration of minerals in cereals, including selection for genotypes with high micronutrient use efficiency, intercropping with legumes, field application of micronutrients as chemical fertilizers, and utilization of beneficial microorganisms [12,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, numerous studies have focused on the qualitative aspects of wheat production to face the widespread malnutrition due to the lack of nutrients in the diet, which leads to the development of pathologies [13][14][15]. There are several biofortification strategies for increasing the concentration of minerals in cereals, including selection for genotypes with high micronutrient use efficiency, intercropping with legumes, field application of micronutrients as chemical fertilizers, and utilization of beneficial microorganisms [12,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of wheat flour with different treatments. Data are from references(22,23,29,37,38,42,45,(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69). Letters a, b, and c indicate a significant difference at the level of P < 0.05; n is the total number of samples.…”
mentioning
confidence: 99%
“…Examples may continue for different products: mushroom sausages [110], mushroom powder pastes [118], marc bread [119], chestnut flour bread [120], spirulina paste [121], inulin-and lactobacilli-fortified juice [122], tortillas fortified with iron and folic acid [123,124], bread fortified with zinc and iron [19], etc.…”
Section: Results Obtained In Food Fortificationmentioning
confidence: 99%
“…A study by Wu [17] based on the consumption of common wheat biscuits biofortified with selenium through fertilization showed that although the levels of selenium in blood plasma increased, there were no significant changes of degenerative disease-specific biomarkers and of the health condition in general. Another method of biofortification that aimed at the development of wheat varieties enriched with some micronutrients was based on interactions between genotypes and environmental factors and led to good iron and zinc levels in humans [18,19].…”
Section: Biofortificationmentioning
confidence: 99%